Cytokine profiles and CD8+ T cells in the occurrence of acute and chronic hepatitis B - Xie, Si; Yang, Liu; Bi, Xiaoyue; Deng, Wen; Jiang, Tingting; Lin, Yanjie; Wang, Shiyu; Zhang, Lu; Liu, Ruyu; Chang, Min; Wu, Shuling; Gao, Yuanjiao; et al. (Frontiers in Immunology, 2022)
Objective To investigate the expression of functional molecules on CD8+ T cells, cytokines concentration, and their correlation to occurrence of hepatitis B and alanine aminotransferase (ALT), hepatitis B virus (HBV) desoxyribose nucleic acid (DNA), hepatitis B surface antigen (HBsAg), hepatitis B envelope antigen (HBeAg) in HBV infected patients. Methods 30 chronic HBV infected patients in immune tolerant (IT) phase, 50 chronic hepatitis B (CHB) patients, and 32 acute hepatitis B (AHB) patients were enrolled. The activation molecules (CD69) and the apoptosis-inducing molecules (CD178) on surface of CD8+ T cells were detected by flow cytometry. The levels of cytokines, including fms-like tyrosine kinase 3 ligand (Flt-3L), interferon (IFN)-α2, IFN-γ and interleukin (IL)-17A, were quantitated by Luminex assay. Their correlations to ALT, HBV DNA, HBsAg, and HBeAg were analyzed by linear regression analysis. Results The frequency of CD69+CD8+ T cells in CHB and AHB groups were increased significantly compared with IT group (4.19[3.01, 6.18]% and 4.45[2.93, 6.71]% vs. 3.02[2.17, 3.44]%; H=26.207, P=0.001 and H=28.585, P=0.002), and the mean fluorescence intensity (MFI) of CD69 in AHB group was increased significantly compared with IT and CHB groups (27.35[24.88, 32.25] vs. 20.45[19.05, 27.75] and 23.40[16.78, 28.13]; H=25.832, P=0.005 and H=22.056, P=0.008). In IT group, HBsAg and HBV DNA were negatively correlated with CD69MFI (β=-0.025, t=-2.613, P=0.014; β=-0.021, t=-2.286, P=0.030), and HBeAg was negatively correlated with the frequency of CD69+CD8+ T cells (β=-61.306, t=-2.116, P=0.043). In AHB group, IFN-α2 was positively correlated with the frequency of CD8+ T cells (β=6.798, t=2.629, P=0.016); however, in CHB group, IFN-α2 was negatively correlated with the frequency of CD8+ T cells (β=-14.534, t=-2.085, P=0.043). In CHB group, HBeAg was positively correlated with the frequency of CD69+CD8+ T cells (β=43.912, t=2.027, P=0.048). In AHB group, ALT was positively correlated with CD69MFI (β=35.042, t=2.896, P=0.007), and HBsAg was negatively correlated with CD178MFI (β=-0.137, t=-3.273, P=0.003). Conclusions The activation of HBV-specific CD8+ T cells was associated with the occurrence of CHB and AHB. However, due to the insufficient expression of functional molecules of CD8+ T cells and the depletion of CD8+ T cells, CHB patients were difficult to recover form HBV infection.